Logotherapy Sebagai Intervensi Keperawatan terhadap Psikologis pada Pasien Kanker - Romadiansyah, Zulfitrah; Wahyuni, Sri; Huda, Nurul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine and analyze logotherapy as a nursing intervention for the psychological condition of cancer patients. The method used is a systematic review obtained from various online databases from 2019-2024, namely Google Scholar, ScienceDirect, and Proquest with the English search keyword